Formation Of Akhlakul Karimah At Sd Muhammadiyah Ngijon 4 Minggir Sleman Yogyakarta - Rini Dwi Hastuti; Ahmad Agung Yuwono Putro (Al-Makki Publisher, 2023)
This study aims to describe in detail the formation of akhlakul karimah at SD Muhammadiyah Ngijon 4 Minggir Sleman Yogyakarta. SD Muhammadiyah Ngijon 4 Minggir Sleman Yogyakarta is an elementary school under the auspices of the DIKDASMEN of the Muhammadiyah Association which has the characteristic of being an Islamic-cultured school identity so that in the education process by applying Islamic values and culture at school. This research is a descriptive qualitative research. Data collection was conducted using interview techniques, observation, and document review. Based on the data obtained, it can be seen that the program that is the determination for the school into buildkhlakul karimah is: 1) Islamic school culture that focuses on cultivating religious characters, openness, caring, togetherness, and cooperation; 2) disciplinary culture with a focus on cultivating characters including religion, discipline, caring, and togetherness.